2020
DOI: 10.1101/2020.09.14.296442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microfluidic Antibody Affinity Profiling for In-Solution Characterisation of Alloantibody - HLA Interactions in Human Serum

Abstract: The detection and characterisation of antibodies in human blood is a key for clinical diagnostics and risk assessmentn for autoimmunity, infectious diseases and transplantation. Antibody titre derived from immunoassays is a commonly used measure for antibody response, but this metric does not resolve readily the two fundamental properties of antibodies in solution, namely their affinity and concentration. This difficulty originates from the fact that the fundamental parameters describing the binding interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 72 publications
2
46
0
Order By: Relevance
“…Moreover, our binding equilibria are thus achieved under physiologically relevant conditions and our in-solution measurements allow to determine both the antibody affinity and concentration. As discussed previously 20 Points correspond to the maximum probability values in the two-dimensional probability distribution, and shaded regions to the probability density. In line with physical principles of binding, binding is not observed for samples with [Ab] < 2Kd (dark grey region).…”
Section: Determination Of Antibody Affinity and Concentration In Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our binding equilibria are thus achieved under physiologically relevant conditions and our in-solution measurements allow to determine both the antibody affinity and concentration. As discussed previously 20 Points correspond to the maximum probability values in the two-dimensional probability distribution, and shaded regions to the probability density. In line with physical principles of binding, binding is not observed for samples with [Ab] < 2Kd (dark grey region).…”
Section: Determination Of Antibody Affinity and Concentration In Plasmamentioning
confidence: 99%
“…Here we determined affinity and concentration directly in plasma samples of seropositive individuals using Microfluidic Antibody Affinity Profiling (MAAP) 20 . We quantified both parameters in 39 seropositive individuals who presented either mild symptoms or were asymptomatic, demonstrating a comparable immune response which is independent of the symptoms displayed.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the K D of anti-S1 antibody-S1 binding, we mixed fluorescently labeled S1 at a constant concentration with patient serum at various dilutions and determined R h as an indicator of complex formation (Figures 3A and C). Since the anti-S1 antibody concentration in the two patient sera was unknown, we extracted this information from the equilibrium binding isotherms by using the concentration of antibody-binding sites as a fitting parameter 21,22 . To obtain well-constrained binding-site concentrations, we measured antibody-binding isotherms at three different concentrations of fluorescently labeled S1.…”
Section: Microfluidic Antibody-affinity Profiling and Neutralization mentioning
confidence: 99%
“…A MAAP study on a larger number of patient samples showed a similar range of affinities among anti-spike serum antibodies 21 . To investigate the robustness of the K D values derived by the global fits, we also analyzed the data using Bayesian inference 21,22 . While the agreement of Bayesian inference with the global fits was excellent, in both patient samples the posterior probability for the K D distribution provided strong constraints for the upper bound but weak constraints for the lower bound, thus providing an upper limit on the K D value and indicating a tight binding interaction.…”
Section: Microfluidic Antibody-affinity Profiling and Neutralization mentioning
confidence: 99%
See 1 more Smart Citation